2023
DOI: 10.1136/bmjopen-2022-069429
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative study evaluating the expectations and experiences of Dutch parents of children with chronic gastrointestinal symptoms visiting their general practitioner

Abstract: ObjectivesChronic gastrointestinal symptoms are common among children and affect their daily activities and quality of life. The majority will be diagnosed with a functional gastrointestinal disorder. Effective reassurance and education are, therefore, key components of the physician’s management. Qualitative studies have shown how parents and children experience specialist paediatric care, yet less is known about general practitioners (GPs), who manage most cases in the Netherlands and have a more personal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Other studies showed that children with chronic abdominal pain continue to have symptoms later in life [ 31 , 32 ], suffer from school absenteeism [ 12 ], anxiety [ 12 , 33 ] and depression [ 33 ]. Follow-up could help the GP to develop a good doctor-patient relationship [ 34 ] and offer effective continuity of care, two important principles required for the often long-term care of these children [ 35 ]. A recent Norwegian interview study confirmed that GPs find it important to build a good relationship with (parents of) children with FGID [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that children with chronic abdominal pain continue to have symptoms later in life [ 31 , 32 ], suffer from school absenteeism [ 12 ], anxiety [ 12 , 33 ] and depression [ 33 ]. Follow-up could help the GP to develop a good doctor-patient relationship [ 34 ] and offer effective continuity of care, two important principles required for the often long-term care of these children [ 35 ]. A recent Norwegian interview study confirmed that GPs find it important to build a good relationship with (parents of) children with FGID [ 36 ].…”
Section: Discussionmentioning
confidence: 99%